Economía circular para la gestión y aprovechamiento de residuos sólidos provenientes del sector de la construcción en Bogotá D.C. (2021)
Solid waste from the construction sector generates a serious problem, since at present there is no efficient management plan that allows it to be reused. Faced with such a situation, a notable volumetric increase of garbage is observed, being found in inappropriate places of disposal. Based on these events, it is necessary to establish the importance of methods for making use of waste from this sector, to reduce its quantity significantly and obtain techniques that promote social, economic and environmental environments. Therefore, the circular economy is proposed as a strategy that provides the ability to generate added value to the waste produced, taking into account the impacts they cause.